Professional Capital as Accountability - Michael Fullan; Santiago Rincón-Gallardo; Andy Hargreaves (Arizona State University, 2015)
This paper seeks to clarify and spells out the responsibilities of policy makers to create the conditions for an effective accountability system that produces substantial improvements in student learning, strengthens the teaching profession, and provides transparency of results to the public. The authors point out that U.S. policy makers will need to make a major shift from a heavy reliance on external accountability and superficial structural solutions (e.g., professional standards of practice) to investing in and building the professional capital of all teachers and leaders throughout the system. The article draws key lessons from highly effective school systems in the United States and internationally to argue that the priority for policy makers should be to lead with creating the conditions for internal accountability, that is, the collective responsibility within the teaching profession for the continuous improvement and success of all students. This approach is based on the development and circulation of professional capital that consists of three components: individual human capital, social capital (where teachers learn from each other), and decisional capital (developing judgment and expertise over time). In this new professional accountability model, the external accountability that reassures the public that the system is performing in line with societal expectations continues to be an important role of educational systems, but it is nurtured and sustained by the development of strong internal accountability.